A complex remodeling of cellular homeostasis distinguishes RSV/SARS-CoV-2 co-infected A549-hACE2 expressing cell lines - Claudia Vanetti; Irma Saulle; Valentina Artusa; Claudia Moscheni; Gioia Cappelletti; Silvia Zecchini; Sergio Strizzi; Micaela Garziano; Claudio Fenizia; Antonella Tosoni; Martina Broggiato; Pasquale Ogno; et al. (Microbial Cell)
Concurrent infections with two or more pathogens with analogous tropism, such as RSV and SARS-CoV-2, may antagonize or facilitate each other, modulating disease outcome. Clinically, discrepancies in the severity of symptoms have been reported in children with RSV/SARS-CoV-2 co-infection. Herein, we propose an in vitro co-infection model to assess how RSV/SARS-CoV-2 co-infection alters cellular homeostasis. To this end, A549-hACE2 expressing cells were either infected with RSV or SARS-CoV-2 alone or co-infected with both viruses. Viral replication was assessed at 72 hours post infection by droplet digital PCR, immunofluorescence, and transmission electron microscopy. Anti-viral/receptor/autophagy gene expression was evaluated by RT-qPCR and confirmed by secretome analyses and intracellular protein production. RSV/SARS-CoV-2 co-infection in A549-hACE2 cells was characterized by: 1) an increase in the replication rate of RSV compared to single infection; 2) an increase in one of the RSV host receptors, ICAM1; 3) an upregulation in the expression/secretion of pro-inflammatory genes; 4) a rise in the number and length of cellular conduits; and 5) augmented autophagosomes formation and/or alteration of the autophagy pathway. These findings suggest that RSV/SARS-CoV-2 co-infection model displays a unique and specific viral and molecular fingerprint and shed light on the viral dynamics during viral infection pathogenesis. This in vitro co-infection model may represent a potential attractive cost-effective approach to mimic both viral dynamics and host cellular responses, providing in future readily measurable targets predictive of co-infection progression.